2011
DOI: 10.1093/carcin/bgr218
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenol EGCG suppresses lung cancer cell growth through upregulating miR-210 expression caused by stabilizing HIF-1 

Abstract: (-)-Epigallocatechin-3-gallate (EGCG) has been reported to affect many cellular regulatory pathways. This study aims to determine whether EGCG could target microRNA (miRNA), one of the mechanisms for cells to achieve subtle change in multiple targets. We found that, in both human and mouse lung cancer cells in culture, EGCG specifically upregulated the expression of miR-210, a major miRNA regulated by HIF-1α. Furthermore, we found that overexpression of miR-210 led to reduced cell proliferation rate and anchor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
157
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(162 citation statements)
references
References 47 publications
3
157
0
2
Order By: Relevance
“…Similarly, EGCG from green tea has been shown to exert potent anti-tumour activity in several types of leukaemia (Lung et al, 2002;Lee et al, 2004), prostate cancer (Siddiqui et al, 2011;Lee et al, 2012), cervical cancer (Ahn et al, 2003), colon cancer (Shimizu et al, 2005), lung cancer (Milligan et al, 2009;Wang et al, 2011;Liu et al, 2012), breast cancer (Sen and Chatterjee, 2011) and pancreatic cancer (Tang et al, 2012). However, clinical application of EGCG has been hampered by its limited solubility and efficacy in patients with cancer, underlining the need for the development of potent EGCG derivatives with improved metabolic stability and greater anti-cancer efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, EGCG from green tea has been shown to exert potent anti-tumour activity in several types of leukaemia (Lung et al, 2002;Lee et al, 2004), prostate cancer (Siddiqui et al, 2011;Lee et al, 2012), cervical cancer (Ahn et al, 2003), colon cancer (Shimizu et al, 2005), lung cancer (Milligan et al, 2009;Wang et al, 2011;Liu et al, 2012), breast cancer (Sen and Chatterjee, 2011) and pancreatic cancer (Tang et al, 2012). However, clinical application of EGCG has been hampered by its limited solubility and efficacy in patients with cancer, underlining the need for the development of potent EGCG derivatives with improved metabolic stability and greater anti-cancer efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG), a major component of green tea polyphenols, has antioxidant (Hu et al, 2009), anti-inflammatory (Peairs et al, 2010), and anti-tumour (Davenport et al, 2010;Wang et al, 2011;Lee et al, 2012;Tang et al, 2012) activity in various cancer cells through the regulation of major cell signalling proteins such as the EGF receptor (Masuda et al, 2001;Ma et al, 2014) and STAT3. EGCG interacts directly with the STAT3 SH2 domain (Wang et al, 2013) to stimulate caspase activation (Gupta et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…39,42) microRNA-210 in particular, has been well studied for its effects in rescuing cardiac function after myocardial infarcts via the upregulation of angiogenesis and inhibition of cardiomyocyte apoptosis. 45) Recent years, accumulated data show that it is significantly upregulated in various kinds of tumors, such as Head and Neck Paragangliomas, 46) lung cancer cells, 47) breast cancer cells. 48) Previous report revealed that overexpression of microRNA-210 could promote the survival of mesenchymal stem cells (MSCs) exposed to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…42 miRNAs can be modulated by botanicals in lung cancer. [43][44][45][46] The effects of curcumin on a human retinal pigment epithelial cell line, ARPE-19, included downregulation of 20 and upregulation of 9 miRNAs. 47 Effects of resveratrol on miRNA have also been studied.…”
mentioning
confidence: 99%